REMEDYING THE DEFECTS IN INDIA’S CREDIT AND INSOLVENCY FRAMEWORKS WITH ADAPTED SOLUTIONS FROM THE ANGLO-AMERICAN LEGAL SCHOLARSHIPS - Iheme, Williams Chima (Pravni zapisi, 2020)
The law governing credit transactions in India is compartmentalized and concomitantly poses difficulties to contractual parties and access to credit: the overall effect of this is already being felt owing to the country’s low rank on the ‘getting credit’ indicator of the World Bank’s Ease of Doing Business Report 2020. The Insolvency and Bankruptcy Code 2016 (Code), being almost a mirror-image of the English Insolvency Act 1986, has some inherent defects that are incompatible with the local conditions vis-à-vis access to credit and business rescue. Some of these defects arguably emanate from the Code’s unfair categorization of creditors into the ‘operational’ and ‘financial’ types, and the ensuing confusion as was witnessed in the Supreme Court’s Home Buyers’ case in 2019. Strangely, financial creditors enjoy some Code-given preferential treatments over operational creditors including the right to constitute committees of creditors in voting and confirming business rescue plans. The insolvency resolution process of the Code is incompatible with the fact that over 90% of the companies doing business in India are SMEs and family-owned. The crushing financial weight of insolvency resolution processes is foreseen to gradually cannibalize these SMEs and cause a sharp rise in the unemployment rate. The article diagnoses a number of defects in the credit and insolvency systems of India, and proposes transplantable solutions from the English system, the U.S. Chapter 11, and Article 9 of the Uniform Commercial Code.
Keywords: credit; collateral; debt; security; business rescue; insolvency; creditor; debtor; law reform